Desarrollo larval de Chrysomya megacephala (Diptera: Calliphoridae) en diferentes dietas y densidades larvales - Aguirre-Gil, Oniel Jeremías [UNESP]; Valente, Fabricio Iglesias [UNESP]; dos Santos, Leticia Serpa [UNESP]; Viana, Daniela de Lima [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2015)
Globally, a third of the edible parts of food produced for human consumption are wasted, therefore it is important the generation of proposals for the sustainable use thereof. The objective of this investigation was to determine the influence of four diets, based in rice bran, in three quantities and three larval densities on the duration of larval period, larval viability and larval weight of C. megacephala. The results indicate that the duration of larval period and percentage of larval viability were favored when the content of rice bran in the diet was increased. In contrast, the larval weight was decreased. In relation with larval density, 5 larvae/g of diet presented the greatest percentage of larval viability, without significant effects on the duration of larval period and larval weight. The duration of larval period and larval viability did not differ by increasing the quantity of diet, while the larval weight increased favorably. In relation with the interaction of factors, the duration of larval period decreased as the larval density increased, in the diet with the greatest content of rice bran, and the larval weight increased as the quantity of diet increased. Finally, the density of 5 larvae/g of diet is the ideal density of C. megacephala, the larval weight increases with the quantity of diet, and the duration of larval period is inversely proportional to the larval density in the diet with the greatest content of rice bran.
Larval development of Chrysomya megacephala (Diptera: Calliphoridae) on different diets and larval densities
Keywords: Blowflies; Larval production; Sustainable development